Respuesta :

Answer:

A. [tex]A = \frac{1}{2}\cdot \sqrt{(x_{2}^{2}+y_{2}^{2})\cdot (x_{2}^{2}+y_{2}^{2})}[/tex]

Step-by-step explanation:

From Geometry, we know that the area of the triangle ([tex]A[/tex]) is equal to:

[tex]A = \frac{1}{2}\cdot b\cdot h[/tex] (1)

Where:

[tex]b[/tex] - Base.

[tex]h[/tex] - Height.

By Pythagorean Theorem, we derive expressions for the base and the height of triangle. That is:

[tex]h = \sqrt{(-x_{1}-0)^{2}+(y_{1}-0)^{2}}[/tex]

[tex]h = \sqrt{x_{1}^{2}+y_{1}^{2}}[/tex] (2)

[tex]b = \sqrt{(x_{2}-0)^{2}+(y_{2}-0)^{2}}[/tex]

[tex]b = \sqrt{x_{2}^{2}+y_{2}^{2}}[/tex] (3)

By (2) and (3), we expand (1):

[tex]A = \frac{1}{2}\cdot \sqrt{(x_{2}^{2}+y_{2}^{2})\cdot (x_{2}^{2}+y_{2}^{2})}[/tex]

Hence, correct answer is A.